2021
DOI: 10.1002/adfm.202103359
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Drug Delivery into Skin Using a Biphasic Dissolvable Microneedle Patch with Water‐Insoluble Backing

Abstract: Dissolvable microneedle patches (MNPs) enable simplified delivery of therapeutics via the skin. However, most dissolvable MNPs do not deliver their full drug loading to the skin because only some of the drug is localized in the microneedles (MNs), and the rest remains adhered to the patch backing after removal from the skin. In this work, biphasic dissolvable MNPs are developed by mounting water-soluble MNs on a water-insoluble backing layer. These MNPs enable the drug to be contained in the MNs without migrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 43 publications
0
13
0
Order By: Relevance
“…Next, a two-step casting procedure was used to prepare the detachable MN patches with their needles composed of MTX/EGCG-HP gel and their supporting arrays made from PVA/PVP. , Each MN patch had an array of 10 × 10 needles with a distance of 500 μm between the centers of two adjacent needle bases. The dermoscopic images showed that the MNs had a square pyramid shape, with a height of 650 μm and a base diameter of 200 μm (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%
“…Next, a two-step casting procedure was used to prepare the detachable MN patches with their needles composed of MTX/EGCG-HP gel and their supporting arrays made from PVA/PVP. , Each MN patch had an array of 10 × 10 needles with a distance of 500 μm between the centers of two adjacent needle bases. The dermoscopic images showed that the MNs had a square pyramid shape, with a height of 650 μm and a base diameter of 200 μm (Figure a,b).…”
Section: Resultsmentioning
confidence: 99%
“…The conventional acne treatments mainly include the epidermal administration of antibiotics or the physical puncture to drain out the pus from lesion. However, repeated applications of antibiotics may reduce the sensitivity of bacteria to drugs ( 2 , 6 , 9 ). In addition, the treatment efficiency can be potentially reduced due to the permeability of epidermal barrier.…”
Section: Discussionmentioning
confidence: 99%
“…We believe that the treatment via ROS-enabled MNs, regarding as a minimal invasive and transdermal approach, can effectively relieve the acne infection ( 8 ). MNs serving as the delivery vehicle of antibiotics or nonantibiotic substances to address bacterial infection have been studied ( 4 , 9 , 15 ). In the current design, we introduce ultrasound-responsive antibacterial nanomaterials to the MN patch that not only responds to bacterial infection quickly and efficiently but also are able to regulate the epidermal repair driven by fibroblasts.…”
Section: Discussionmentioning
confidence: 99%
“…Biomaterial-Based Microneedles: Biomaterial-based microneedles have been investigated for decades in biomedicine for transdermal and intradermal drug delivery and vaccination as an easily deployable, rapid, pain-free method to overcome the drug delivery barrier imposed by the skin's outer stratum corneum layer. [98][99][100] Similar principles are now applied to plants, where the use of microneedles has been recently demonstrated. Although steel microneedles were proposed to increase bark permeability for agrochemical delivery [101] as used for medical applications, polymeric microneedles are now more investigated, given their versatile encapsulation of payloads and materials safety and sustainability.…”
Section: Biomaterial-based Precision Delivery Systemsmentioning
confidence: 99%